2001
DOI: 10.1182/blood.v97.7.1999
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic effects of a tyrosine kinase inhibitor STI571 in combination with commonly used antileukemic agents

Abstract: The BCR/ABL tyrosine kinase has been implicated in the pathogenesis of chronic myelogenous leukemia (CML) and Philadelphia chromosome-positive (Ph ؉ ) acute lymphoblastic leukemia (ALL). STI571 is a novel anticancer agent that selectively inhibits the BCR/ABL tyrosine kinase. The cytotoxic effects of STI571 were studied in combination with antileukemic agents against Ph ؉ leukemia cell lines, KU812, K-562, TCC-S, and TCC-Y. The cells were exposed to STI571 and to other agents simultaneously for 5 or 7 days. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
1
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(159 citation statements)
references
References 28 publications
6
147
1
5
Order By: Relevance
“…Overall, our findings are in general agreement with similar reports of drug interactions between STI571 and anti-leukaemic agents that have been published in the last year (Thiesing et al, 2000;Kano et al, 2001;Topaly et al, 2001). While these studies only stopped at highlighting a synergistic reduction in absolute cell number, we went on to specifically identify hyper-additive increases in apoptosis.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our findings are in general agreement with similar reports of drug interactions between STI571 and anti-leukaemic agents that have been published in the last year (Thiesing et al, 2000;Kano et al, 2001;Topaly et al, 2001). While these studies only stopped at highlighting a synergistic reduction in absolute cell number, we went on to specifically identify hyper-additive increases in apoptosis.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 92%
“…Additionally, subsequent flow cytometric analysis showed that cell kill was by apoptosis, occurring from all phases of the cell cycle. These ICvalues were higher than those reported in recent synergy studies (Thiesing et al, 2000;Kano et al, 2001;Topaly et al, 2001). Methodologically, the activity of STI571 in combination in these studies was assessed by the MTT assay, which is strictly a technique for measuring cell number and not cell kill (Carmichael et al, 1987).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 83%
“…Whilst similar data have been published for the drug responses of imatinib-sensitive cell lines, [18][19][20][21] to our knowledge this work represents the first investigation of the effect of acquired resistance to imatinib on these drug responses. LAMA84-r showed some cross-resistance to these drugs relative to the sensitive line, but the levels of anti-proliferative effect obtained are still generally substantial.…”
Section: Discussionmentioning
confidence: 63%
“…18 On the basis of dose-response curves of the two drugs, three isoeffect curves were constructed. The area surrounded by the isoeffect curves was referred as the envelope of additivity.…”
Section: Isobolographic Analysis For Determination Of Synergymentioning
confidence: 99%